Higher Muscle Strength Is Associated with Prolonged Survival in Older Patients with Advanced Cancer - Versteeg, Kathelijn Sophie (Oncologist, 2017)
BACKGROUND. Identifying predictors of treatment toxicity and overall survival (OS) is important for selecting patients who will benefit from chemotherapy. In younger patients with cancer, muscle mass and radiodensity are associated with treatment toxicity and OS. In this study, we investigated whether muscle mass, radiodensity, and strength were associated with treatment toxicity and OS in patients with advanced cancer aged 60 years or older. MATERIALS AND METHODS. Before starting palliative chemotherapy, muscle mass and radiodensity were assessed using computed tomography scans and muscle strength was assessed using a hydraulic hand grip dynamometer. Treatment toxicity was defined as any toxicity resulting in dose reduction and/or discontinuation of treatment. Multiple logistic and Cox regression analyses were performed to study potential associations of muscle mass, radiodensity, and strength with treatment toxicity and OS, respectively. RESULTS. The participants were 103 patients, with a mean age of 70 years, with advanced colorectal, prostate, or breast cancer. Muscle parameters were not significantly associated with treatment toxicity. Higher muscle strength was associated with longer OS (hazard ratio 1.03; 95% confidence interval 1.00–1.05). Muscle mass and radiodensity were not significantly associated with OS. CONCLUSION. Higher muscle strength at the start of palliative chemotherapy is associated with significantly better OS in older patients with advanced cancer. None of the investigated muscle parameters were related to treatment toxicity. Future studies are needed to evaluate whether muscle strength can be used for treatment decisions in older patients with advanced cancer. IMPLICATIONS FOR PRACTICE. This study in older patients with advanced cancer showed that adequate muscle strength is associated with longer overall survival. The results of this study imply that muscle strength might be helpful in estimating survival and therefore in identifying older patients who will benefit from anticancer treatment.